Discovery of diamide compounds as diacylglycerol acyltransferase 1 (DGAT1) inhibitors. Issue 4 (15th February 2016) - Nakajima, Katsumasa; April, Myriam; Brewer, Jason T.; Daniels, Thomas; Forster, Cornelia J.; Gilmore, Thomas A.; Jain, Monish; Kanter, Aaron; Kwak, Youngshin; Li, Jingzhou; McQuire, Les; Serrano-Wu, Michael H.; et al.
Graphical abstract: Abstract: Diamide compounds were identified as potent DGAT1 inhibitors in vitro, but their poor molecular properties resulted in low oral bioavailability, both systemically and to DGAT1 in the enterocytes of the small intestine, resulting in a lack of efficacy in vivo. Replacing an N -alkyl group on the diamide with an N -aryl group was found to be an effective strategy to confer oral bioavailability and oral efficacy in this lipophilic diamide class of inhibitors.